Effects of petrochemical contamination on caged marine mussels using a multi-biomarker approach: Histological changes, neurotoxicity and hypoxic stress. (July 2017) - Maisano, Maria; Cappello, Tiziana; Natalotto, Antonino; Vitale, Valeria; Parrino, Vincenzo; Giannetto, Alessia; Oliva, Sabrina; Mancini, Giuseppe; Cappello, Simone; Mauceri, Angela; Fasulo, Salvatore
Abstract: This work was designed to evaluate the biological effects of petrochemical contamination on marine mussels. Mytilus galloprovincialis, widely used as sentinel organisms in biomonitoring studies, were caged at the "Augusta-Melilli-Priolo" industrial site (eastern Sicily, Italy), chosen as one of the largest petrochemical areas in Europe, and Brucoli, chosen as reference site. Chemical analyses of sediments at the polluted site revealed high levels of PAHs and mercury, exceeding the national and international guideline limits. In mussels from the polluted site, severe morphological alterations were observed in gills, mainly involved in nutrient uptake and gas exchange. Changes in serotonergic and cholinergic systems, investigated through immunohistochemical, metabolomics and enzymatic approaches, were highlighted in gills, as well as onset of hypoxic adaptive responses with up-regulation of hypoxia-inducible factor transcript. Overall, the application of a multi-biomarker panel results effective in assessing the biological effects of petrochemical contamination on the health of aquatic organisms. Highlights: Biological effects of petrochemical contamination were evaluated in caged mussels. Chemical analysis revealed elevated levels of PAHs and Hg in sediment samples. Marked morphological changes were observed in gills of mussels from polluted area. Changes in neurotransmission and onset of hypoxic adaptive responses were observed. Use of a multi-biomarker panel is effective to assess the health status of biota.